An alternative board game to promote EFL learners grammatical skill - Hayatul Mila; Moh Arif Mahbub (Universitas Merdeka Malang, 2022)
Gamificatian has been acknowledged as a powerful tool to promote the conducive and attractive learning environment. Recenly, extensive research has been carried out on the role of gamification in facilitating languages learners. Yet, little research has taken to explore the undergraduate students about the incorporation of gamification into English grammar classroom in Indonesian tertiary-level. We employed a sequential-explanatory research ( Creswell, 2014; J. W. Creswell, 2018) intended to explore in-depth the undergraduate students’ perceptions about the use of Gamification in such context. There were four (N=4) undergraduate students from one private university in Jember, Indonesia, consented to participate in this study. They were invited to fill a 9-items web-based five points-Likert scale questionnaire covering several categories: students’ behavior, motivation and engagement. Also, a semi-structure interview was conducted to explore their in-depth feelings to select participant. The results indicated that participants mostly demonstrated positive feelings toward the utilization of gamification in grammar classrooms. This study concludes with discussion of implications for teaching-learning grammar in EFL context, limitation and recommendation for future studies. DOI: 10.26905/enjourme.v7i1.7043